2010
DOI: 10.1039/b918849e
|View full text |Cite
|
Sign up to set email alerts
|

Controlling crystal growth with modifiers

Abstract: Modifying crystal growth processes using additives is a well established approach to solving problems in many processes. Nature also makes extensive use of crystalline inorganic structures modified by soluble and insoluble organic materials. This Highlight discusses some of the recent and interesting developments in this area, with an emphasis on the control of crystal growth rates, covering both inhibitors and the lesser known promoters of crystal growth. Hybrid materials resulting from the incorporation of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 47 publications
0
71
0
Order By: Relevance
“…The growth of barium sulfate is sensitive to the supersaturation and this results in morphological changes as S varies [28,29]. The morphology was investigated both at 25 and 75 1C (the increase in temperature of the precipitation increases the effect of kinetics due to the Arrhenius relationship of the rate constant while the thermodynamics, DG, change less significantly with temperature [23]).…”
Section: Resultsmentioning
confidence: 99%
“…The growth of barium sulfate is sensitive to the supersaturation and this results in morphological changes as S varies [28,29]. The morphology was investigated both at 25 and 75 1C (the increase in temperature of the precipitation increases the effect of kinetics due to the Arrhenius relationship of the rate constant while the thermodynamics, DG, change less significantly with temperature [23]).…”
Section: Resultsmentioning
confidence: 99%
“…Possible mechanisms of modifiers which may help to reduce the damage are: (i) keeping salts dissolved in solution (inhibitors) allowing for transport to the surface during evaporation; (ii) promoting the crystallization of a specific crystal phase (promoters) at or near saturation; (iii) changing the shape of the growing crystals (habit modifiers). 30 Beneficial effects of habit modification can for instance be seen in the case of ferrocyanide modification of sodium chloride. Due to the presence of ferrocyanide, the shape of the crystals changes from cubic to dendritic.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, no fungus was found during two months storage at both the conditions. Jones (1987) reported the detrimental influence of mould growth in stored feeds reduced nutritional value owing to the loss of dietary lipids, amino acids (especially lysine and arginine) and vitamins by enzymatic digestion. The value of the initial moisture content in Mega, Quality and Saudi Bangla fish feed were 11.34%, 11.84% and 11.96%, respectively.…”
Section: Resultsmentioning
confidence: 99%